2005
DOI: 10.1063/1.1862236
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio n-electron valence state perturbation theory study of the adiabatic transitions in carbonyl molecules: Formaldehyde, acetaldehyde, and acetone

Abstract: The application of the recently developed second-order n-electron valence state perturbation theory (NEVPT2) to small carbonyl molecules (formaldehyde, acetaldehyde, and acetone) is presented. The adiabatic transition energies are computed for the singlet and triplet n-->pi(*), pi-->pi(*), and sigma-->pi(*) states performing a full geometry optimization of the relevant states at the single state CASSCF level and taking into account the zero point energy correction in the harmonic approximation. The agreement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 77 publications
(33 reference statements)
6
24
0
Order By: Relevance
“…Such discrepancies in theoretical geometrical structure for formaldehyde were also reported in other works (see Refs. [49] and [51] for (6-5) and (12-10) AS within ANO basis set, Ref. [52] for (10-9) AS in DZP basis).…”
Section: Casscfmentioning
confidence: 99%
See 1 more Smart Citation
“…Such discrepancies in theoretical geometrical structure for formaldehyde were also reported in other works (see Refs. [49] and [51] for (6-5) and (12-10) AS within ANO basis set, Ref. [52] for (10-9) AS in DZP basis).…”
Section: Casscfmentioning
confidence: 99%
“…2); this is primarily due to large absolute value of E. Interestingly, SR MP2 method demonstrates the largest E deviation. It should also be noted that NEVPT2 transition energies for formaldehyde calculated using CASSCF (6-5) and (12-10) geometry together with ANO basis [51] slightly agree slightly better with experimental Table VIII; for F 2 CO (S 1 ), experimental barrier of 6000 cm Ϫ1 was assumed. [Color figure can be viewed in the online issue, which is available at www.interscience.wiley.com.]…”
mentioning
confidence: 99%
“…20 The calculation of the adiabatic π → π * transition energy is also problematic in the small carbonyl molecules. 21 The description of the π → π * ionic excited states presents difficulties also in the aromatic molecules, as has been recognized since the first ab initio studies (see for instance refs. 22 26 ) have confirmed that these states present peculiar problems.…”
Section: Introductionmentioning
confidence: 98%
“…The most recent theoretical studies clearly establish the nature of the excited states. 13,15 In the present study we have employed the TD-B3LYP/6-311+G(3df,2p) method on geometries optimised at the B3LYP/6-31G(d) level whenever possible. The calculated excitation energies are shown in Table 1.…”
Section: The Excited States Of Formaldehydementioning
confidence: 99%